Economic recovery in Africa : the paradox of financial flows - Makhan, Vijay S., 1948- (New York : Palgrave, 2002)
Contends that insufficient financial resources are the biggest block to economic development in Africa now that good macroeconomic policies are in place in much of the continent. With little savings, minimal export earnings growth, and an external debt burden, these countries cannot finance their development. In addition, very little foreign investment goes into African countries, and official development finance has been declining in both real and nominal terms since the early 1990s. .
Includes bibliographical references (p. 225-231) and index.
oif 17/09/15
Loan
Keywords: Africa -- Economic policy; Economic assistance -- Africa; Flow of funds -- Africa